Effectiveness of Proprioceptive Neuromuscular Facilitation (PNF) Exercises in Upper Limb Motor Function Recovery in Patients with Stroke: A Randomized Clinical Trial - Md Saifur Rahman (Journal of Bioscience & Biomedical Engineering, 2026)
Stroke is a global epidemic as the most common brain disorders all over the world. Motor impairment is one of the most common challenging outcomes of upper extremity after stroke. Proprioceptive Neuromuscular Facilitation has been reported to have beneficial effects on different aspects in stroke survivors; how-ever, there is limited information about its effects on pain, upper limb motor function and fine motor activity, coordination and hand function. Therefore, our aim is to investigate the effectiveness of PNF exercise combined with conventional physiotherapy on enhancing upper limb motor function, fine motor activity, coordination, muscle tone and reducing pain in stroke patients and compare the findings to those of usual physiotherapy in stroke survivors. A single-center, parallel, assessor, and participant-blinded randomized clinical trial were conducted. A total of 68 stroke survivors were randomized to experimental group and control group. Both groups underwent 24 treatment sessions over six weeks The experimental group received proprioceptive neuromuscular facilitation patterns for the neck, trunk, scapula and upper extremity with conventional physiotherapy, whereas the control group received only conventional physiotherapy. This study conducted a pre-test (before the intervention) and a post-test (subsequent after the intervention) for each participant in both groups to evaluate the upper limb motor function, including pain, strength, coordination, fine motor activity and muscle tone before and after treatment. The primary outcome was the change in the Numeric Pain Rating Scale and Fugl–Meyer assessment for Upper Extremity scores and the secondary outcomes were the changes in Action Research Arm Test, Modified Ashworth scale. Statistically significant difference was obtained in favor of the between group. However, both groups showed significant improvement. The findings from this study provides strong evidence for the efficacy of PNF exercise in enhancing upper limb motor function, fine motor activity, coordination, muscle tone and reducing pain in stroke patients when combined with conventional rehabilitation. These results support the integration of PNF exercise into comprehensive stroke rehabilitation programs to optimize upper limb recovery and improve the overall quality of life for stroke survivors.